Agent-based Modeling and Simulation in Archaeology - Wurzer, Gabriel; Kowarik, Kerstin; Reschreiter, Hans (Advances in Geographic Information Science, 2015)
Gabriel Wurzer is a computer scientist working on Agent-Based Simulation at Vienna University of Technology, in which field he is publishing, organizing workshops and holding lectures. Through cooperation with the Natural History Museum Vienna, he developed multiple models on prehistoric salt mining in the prehistoric mines of Hallstatt. Apart from Archaeology, he is also active in the field of Architectural planning, especially Hospital Simulation in the context of early design. Kerstin Kowarik is an archaeologist working at the Natural History Museum Vienna specializing in the European Bronze Age and Early Iron Age. She is currently engaged with several research projects on the prehistoric salt mines of Hallstatt. Her research focuses on provisioning structures, organization of trade and human - environment interaction. She has a special interest in exploring the potential of computer based simulations for archaeological research, economic archaeology and environmental archaeology. Hans Reschreiter is an archaeologist working at the Natural History Museum Vienna specializing in prehistoric crafts and technology as well as prehistoric mining. He is head of the archaeological excavations in the prehistoric salt mines of Hallstatt (Austria). His research focuses on working processes and mining technology. He has a special interest in prehistoric wood working, experimental archaeology and ethnoarchaeology.